Neurozerra conferta Walker. (Beehole Borer) on Aquilaria malaccensis Lamk. in Assam - Borthakur, Nizara D.; Borah, R. K.; Dutta, B. K.; Jayaraj, R. S. C. (Indian Forester, 2021)
Neurozerra conferta Walker. (syn. Zeuzera conferta) a lepidopteran wood borer belonging to the family Cossidae, is an important insect pest on Aquilaria malaccensis Lamk. in Northeast India. It is commonly known as beehole borer. The eggs are laid on the upper portion of the trunk near the branch. The newly hatched larvae enter into the branches or twigs of the tree by making hole through bark. They bore inside the tree trunk making zig-zag tunnels in upward direction, feeding within the tunnel and complete their larval and pupal stages inside the plant and emerge as adults and fly away. The duration of life cycle is 5 to 6 months depending on the temperature. Although Neurozerra conferta is a polyphagous pest of mangrove forests in Bangladesh, in Assam its infestation has been observed only on A. malaccensis. This tree species is renowned for its black oleoresin and its oil which has very high price in international market. Generally, agar wood is harvested by felling the tree and then cutting it down for making chips. Indiscriminate cutting of agar tree in search of agar wood by unskilled persons, has led to its decline in wild. Natural formation of agarwood happens mostly in areas where N. conferta is present, and in other areas artificial induction becomes necessary drilling holes on the tree. To ascertain the role of N. conferta on agarwood formation and to explore possibilities of its cultivation for release in areas where natural agarwood formation does not take place, the biology of the insect was studied in detail. Paucity of information on bio-ecology of N. conferta on A. malaccensis necessitated more observations. The same is presented with illustrations.